SPIRIT TA - Safitri, Novi Angga (IAIN Palangka Raya, 2021)
In the practice of Ta'awun, the traders of Pasar Besar at Palangka Raya City performed it by helping each other in providing and selling the goods needed by buyers, as well as to other fellow traders. However, there were still some traders who did not help each other with other traders because they thought there was business competition. This study attempted to determine the form and constraints of the implementation of Ta'awun spirit of the traders